Aggressive behavior of primary school students In the city of Mosul from the point of view of the post-ISIS teacher - Haider Kamel Nasrawi (Zanco Journal of Humanity Sciences)
The current research aims to identify the aggressive behavior of a sample of students in the elementary stage in the city of Mosul after the occupation of ISIS and that from the teacher's point of view, the aggressive behavior scale was built by following the scientific methodology in preparing and applied electronically to the research sample consisting of (173) students Of them (74 males and 99 females) from fourth, fifth and sixth grades of elementary school in Mosul city schools, the study also aimed to identify the differences in the hostile behavior of the research sample according to the variable of sex, grade and the loss of a family member. The results of the research showed that there is a low level of behavior. Aggressive among the research sample in general, and there were differences in the study variable according to the gender variable and in favor of males, and there were no significant differences in the aggressive behavior according to the school stage, as well as there were differences in the study variable in favor of the one who lost one of his family members, a number of recommendations and proposals were mentioned for approval On the search results.